2017
DOI: 10.1051/0004-6361/201630010
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced direct collapse due to Lyman α feedback

Abstract: We assess the impact of trapped Lyman α cooling radiation on the formation of direct collapse black holes (DCBHs). We apply a one-zone chemical and thermal evolution model, accounting for the photodetachment of H − ions, precursors to the key coolant H 2 , by Lyman α photons produced during the collapse of a cloud of primordial gas in an atomic cooling halo at high redshift. We find that photodetachment of H − by trapped Lyman α photons may lower the level of the H 2 -dissociating background radiation field re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 74 publications
1
18
0
Order By: Relevance
“…Later Smith et al (2016Smith et al ( , 2017a performed self-consistent MCRT Lyα radiation hydrodynamics (RHD) calculations of galactic winds in the first galaxies, finding that direct collapse black holes (DCBHs), which form in primordial gas, foster an environment that is especially susceptible to Lyα feedback. It has subsequently been found that trapped Lyα cooling radiation potentially affects the initial collapse of these massive black hole seeds through chemical (Johnson & Dijkstra 2017) and thermal (Ge & Wise 2017) feedback. To address the limitations of 1D geometry, Smith et al (2017b) performed a post-processing radiative feedback analysis of a DCBH assembly environment, concluding that fully coupled 3D Lyα RHD will be crucial to consider in future DCBH simulations.…”
Section: Eddington Factormentioning
confidence: 99%
“…Later Smith et al (2016Smith et al ( , 2017a performed self-consistent MCRT Lyα radiation hydrodynamics (RHD) calculations of galactic winds in the first galaxies, finding that direct collapse black holes (DCBHs), which form in primordial gas, foster an environment that is especially susceptible to Lyα feedback. It has subsequently been found that trapped Lyα cooling radiation potentially affects the initial collapse of these massive black hole seeds through chemical (Johnson & Dijkstra 2017) and thermal (Ge & Wise 2017) feedback. To address the limitations of 1D geometry, Smith et al (2017b) performed a post-processing radiative feedback analysis of a DCBH assembly environment, concluding that fully coupled 3D Lyα RHD will be crucial to consider in future DCBH simulations.…”
Section: Eddington Factormentioning
confidence: 99%
“…However, in realistic situations, the background radiation spectrum is expected to evolve, and hence both k H − and k H 2 will be changing with time. Moreover, trapping of Lyα photons emitted in an optically-thick accretion flow during the direct collapse can affect the gas cooling (e.g., Schleicher et al 2010;Ge & Wise 2017), and even photodetach most of H − (e.g., Johnson & Dijkstra 2017). Under these conditions, the ratio of k H − to k H 2 cannot be calculated simply.…”
Section: Introductionmentioning
confidence: 99%
“…They found a dense shell-like outflow structure, formed in response to the central ionizing source, and that Lyα radiation pressure may have a significant dynamical impact on gas surrounding DCBHs. Finally, it has also been suggested that trapped Lyα cooling radiation may enhance the formation of DCBHs by facilitating the photodetachment of H − ions, precursors to H 2 , during collapse (Agarwal & Khochfar 2015;Johnson & Dijkstra 2017). However, all Lyα feedback studies thus far have been limited to 1D geometries.…”
Section: Introductionmentioning
confidence: 99%